2002
DOI: 10.2165/00007256-200232030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Levels of Physical Activity in Adults

Abstract: A large proportion of adults in Western cultures are physically inactive, despite several decades of warnings about the potentially negative health consequences of a sedentary lifestyle. Efforts to promote physical activity have focused on identifying its determinants and designing interventions that might effectively promote regular physical activity. The multitude of factors that induce adults to initiate and maintain programmes of physical activity have been divided into those that are invariable (age, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
255
1
23

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(301 citation statements)
references
References 198 publications
22
255
1
23
Order By: Relevance
“…First, physical activity interventions have often been challenged by the need to accurately measure and record data from daily behaviors. [49][50][51][52] Prior studies have relied mostly on either self-reported activity. 52 In this study, physical activity was measured using smartphones, which are already in possession by two-thirds of US adults, 29,30 but have not previously been well evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…First, physical activity interventions have often been challenged by the need to accurately measure and record data from daily behaviors. [49][50][51][52] Prior studies have relied mostly on either self-reported activity. 52 In this study, physical activity was measured using smartphones, which are already in possession by two-thirds of US adults, 29,30 but have not previously been well evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of culture and the acculturation process have been suggested as partial explanations for differences in health outcomes among racial/ethnic groups (as a large number of immigrants are non-White) and differences in health outcomes between immigrants and non-immigrants regardless of racial/ethnic grouping [2]. In the case of obesity, it is hypothesized that aspects of migration (i.e., changes in diet, exercise, stress, cultural norms) may adversely affect body composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, PARS have not been a universal failure with some schemes reporting sustained improvement in clients' physical activity levels and subsequent positive health indicators (NHS, 2001). Success across a number of specific schemes has also been reported (Seefeldt, Malina and Clark, 2002), although scepticism remains over changes in long term lifestyle habits (Riddoch et al 1998;Morgan 2005 (Leijon et al, 2010). Some schemes consider retention as low as 20% to be successful (Cock, Adams, Ibbestson and Baugh, 2008).…”
Section: Physical Activity Referral Schemes (Pars)mentioning
confidence: 99%
“…Support from staff should be consistent and continuous; clients may need to hear a message repeatedly in order to affect behaviour (Isaacs et al, 2007). Clients who are regularly contacted by staff are more likely to maintain their participation (Hillsdon et al 2005;Seefeldt et al 2002).…”
Section: Expertise Staffing and Social Supportmentioning
confidence: 99%
See 1 more Smart Citation